Upaya Meningkatkan Motivasi dan Hasil Belajar IPA Kelas VI Melalui Penerapan Model Dua Tinggal Dua Tamu di SD Negeri 3 Cakranegara - Abdiningsih, Ni Luh Putu (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
This study aims to determine the effectiveness of Duo TT An Competitive Prise model in an effort to improve the motivation and learning outcomes of science students of Class VI SD Negeri 3 Cakranegara. The benefits of this research are to encourage students to develop group learning skills (cognitive) and to socialize with friends in the actual learning process in the classroom. For teachers, the result of the study is to improve the development of approaches and models of learning with the application of scientific and discovery learning strategies in group learning (cooperative) with discussionmethod. This research was conducted in two cycles, and each cycle activity encompassed planning, execution, observation and reflection. The final result of action in cycle II showed that the result of teacher observation equal to 4,64, and the result of student observation reached average score (4,25). The students learning achievement gained average score (82,78), meaning that indicator of the learning success (> 4.0) and the result of learning achievement (> 75,00) had been exceeded. Because the success indicator has been proven that the research is categorizedsuccessful and stopped in cycle II.